Menopause and premature ovarian insufficiency in rheumatic diseases: A review - Taras S. Panevin; Antonina V. Ledina; Evgeniy G. Zotkin (IP Berlin A.V., 2023)
Premature ovarian insufficiency (POI) is a clinical syndrome defined as loss of ovarian function before the age of 40 years. Among the causes of POI are genetic, metabolic disorders, as well as infectious or iatrogenic factors, but in some cases the exact cause cannot be established. Given the possible association of ovarian failure with autoimmune disorders, as well as the detection of antibodies to normal ovarian tissue in the serum of patients with POI, it is assumed that an autoimmune mechanism is a significant cause of the syndrome. Taking into account the relationship between POI and autoimmune diseases, it seems relevant to address the issues of mutual influence of the ovarian function of women with POI and rheumatic diseases (in particular, systemic lupus erythematosus, rheumatoid arthritis and systemic scleroderma), which is presented in this review. Hormone replacement therapy may be recommended for women with POI to improve their quality of life. Keywords: premature ovarian insufficiency, menopause, anti-ovarian antibodies, systemic lupus erythematosus, rheumatoid arthritis, systemic scleroderma, rheumatic diseases, hormone replacement therapy.